Penanaman karakter religious pada siswa Sekolah Dasar melalui pembiasaan shalat dhuha - Sulistyo Rini, Tien (Journal of Innovation in Teaching and Instructional Media, 2021)
Inculcating religious character in elementary school students is very important, because elementary school age is the basis for going to the next level. The purpose of this study was to instill a religious character in elementary school students by performing the Duha prayer at school regularly under the guidance of religious teachers and classroom teachers. This research is a descriptive study conducted at SDN 8 Talang Kelapa, Banyuasin Regency. The data in this study were obtained by direct observation and then described in the form of descriptions. The results of this study indicate that the inculcation of religious character in elementary school students at SDN 8 Talang Kelapa with the habituation of performing dhuha prayers before carrying out learning in class can strengthen the character of students. Thus, this research can be a reference in shaping the religious character of students.